2013
DOI: 10.1093/cvr/cvt080
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic interval training attenuates remodelling and mitochondrial dysfunction in the post-infarction failing rat heart

Abstract: Exercise reduces LV contractile deterioration in post-infarction heart failure and alleviates the extent of mitochondrial dysfunction, which is paralleled with preserved complex I activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 44 publications
4
53
0
10
Order By: Relevance
“…Several studies have demonstrated that exercise training which induced better aerobic capacity confers sustainable protection against cardiovascular diseases in animal models and humans, improving cardiovascular outcome and quality of life Campos et al, 2012;Erbs et al, 2010;Medeiros et al, 2008;Rognmo et al, 2012). Some of the cellular adaptations induced by exercise include mitochondrial biogenesis, improved efficiency of cardiac mitochondrial oxidative phosphorylation, reduced mitochondria permeability transition, elevated antioxidant capacity and induction of myocardial heat shock proteins (Campos et al, 2012;Kraljevic et al, 2013). However, the molecular mechanisms underlying the beneficial effects of exercise training on cardiovascular diseases are still in debate.…”
Section: Exercise Training and Redox Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that exercise training which induced better aerobic capacity confers sustainable protection against cardiovascular diseases in animal models and humans, improving cardiovascular outcome and quality of life Campos et al, 2012;Erbs et al, 2010;Medeiros et al, 2008;Rognmo et al, 2012). Some of the cellular adaptations induced by exercise include mitochondrial biogenesis, improved efficiency of cardiac mitochondrial oxidative phosphorylation, reduced mitochondria permeability transition, elevated antioxidant capacity and induction of myocardial heat shock proteins (Campos et al, 2012;Kraljevic et al, 2013). However, the molecular mechanisms underlying the beneficial effects of exercise training on cardiovascular diseases are still in debate.…”
Section: Exercise Training and Redox Signalingmentioning
confidence: 99%
“…Kraljevic and co-workers have recently demonstrated that aerobic interval training restores mitochondrial respiration in a myocardial infarction-induced heart failure animal model (Kraljevic et al, 2013). However, further studies comparing different exercise training protocols are required.…”
Section: Heart Failurementioning
confidence: 99%
“…In stable chronic heart failure, clinical studies have shown that long-term moderate physical training attenuates abnormal cardiac remodeling and improves functional capacity and quality of life [10,11,12,13]. In different cardiac injury models, exercise has been shown to attenuate left ventricular dilation, myocyte hypertrophy, myocardial fibrosis, mitochondrial dysfunction, myocyte calcium handling changes, sympathoexcitation, cardiac dysfunction, and improve inflammatory profile [14,15,16,17,18,19,20,21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…Exercise is an important clinical intervention for the prevention and treatment of MI [19][21]. It is well established that exercise decreases sympathetic activity after MI [22][24].…”
Section: Introductionmentioning
confidence: 99%